Revisiting the relationship between land price and parcel size - Matthias Ritter; Silke Hüttel; Martin Odening; Stefan Seifert (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2019)
Hedonic land price models often use parcel size as an explanatory variable. Empirical analyses, however, are rather ambiguous regarding the direction and the size of the effect of this variable on farmland values. The objective of this paper is to investigate this size-price relation in detail and to derive recommendations for an appropriate specification of hedonic land price models. Our analysis consists of three steps. First, we conduct a meta-analysis based on a comprehensive literature review. Second, we analyze a dataset of more than 80,000 land transactions in Saxony-Anhalt, Germany, using the non-parametric locally weighted scatterplot smoothing (LOWESS) estimator. This unconditional smoothing algorithm identifies negative size-price relations for very small and large plots, whereas it finds a positive relation for medium plot. We use this finding in our third step, a hedonic land price model, in which the size-price relation is modelled conditional on land and buyer characteristics. From these steps, we conclude that the complex relationship between land price and plot size cannot be captured by a simple functional form since it is affected by several economic factors, such as economies of size, transaction cost, and financial constraints.
Keywords: C12; C14; Q11; Q24; 330; Land Prices; Parcel Size; Hedonic Model; LOWESS